Pentingnya Meningkatkan Kecerdasan Sosial Emosional Pada Anak Usia Dini - Sevi Triana, Rizki; Winnuly, Winnuly; Susanti, Tri (Education Journal : Journal Educational Research and Development, 2024)
This research is motivated by the large number of humans whose intelligence level is good but less likely to achieve success in life, this is due to social and emotional intelligence factors, many people are less likely to achieve success in life. Controlling impulses, less able to manage stress well, less able to communicate well, less able to recognize and solve problems, less able to adapt, and others, therefore it is necessary to carry out studies with cases using several examples of some people who will carry out the education process of their children. The survey was conducted by researchers and asked questions to the nearest community and many responses were varied. This research uses qualitative descriptive research methods combined with a document research technique, with the aim of achieving the desired research results. The results of this study have helped obtain phenomena and data that show that the existence of preschool education institutions is very important in stimulating the development of children's hidden potential, especially aspects of child growth and development, one of which is an emotional and social development of children, especially early childhood.